Intentional methomyl-poisoning of peregrine falcons ( Falco peregrinus ) in Switzerland - Vogler, Barbara; Hoop, Richard; Sinniger, Martin; Albini, Sarah (2021)
The present report describes two proven cases of illegal poisoning of peregrine falcons in the city of Zurich, Switzerland. Both animals died in their eyries after capturing and feeding on a methomyl-laced pigeon. Both eyries are surveillanced by cameras, and the death of one falcon was broadcasted live on the Internet. The city game warden had noticed the disappearance of a brooding female from an artificial eyrie in 2009 and had found five dead falcons at plucking posts or artificial eyries between 2009 and 2013. Owing to these reports in combination with reports on the disappearance of at least eight pairs of peregrine falcons from traditionally used nesting sites in north-western Switzerland since the 1980s, the authors presume that there may be a high number of unreported cases of illegal killing of peregrine falcons in Switzerland. They suggest an increased surveillance, and a coordinated collection of data on wildlife crime may aid the prosecution of perpetrators.